Idiopathic abdominal cocoon syndrome: Preoperative diagnosis with computed tomography - Adnan Karan; Mustafa Özdemir; Mustafa Taner Bostancı; Erdal Birol Bostancı (Turkish Journal of Gastroenterology, 2019)
-